Location of Periventricular Nodular Heterotopia Is Related to the Malformation Phenotype on MRI - González, G.; Vedolin, L.; Barry, B.; Poduri, A.; Walsh, C.; Barkovich, A.J. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Periventricular nodular heterotopia are common malformations of cortical development that are associated with many clinical syndromes and with many different neuroimaging phenotypes. The purpose of this study was to determine whether specific malformation phenotypes may be related to location, side, or number of PNH as assessed by MR imaging. MATERIALS AND METHODS: MR images of 200 patients previously diagnosed with PNH were retrospectively analyzed. PNH were classified according to their location along the ventricles (anterior, posterior, or diffuse), side (unilateral or bilateral), and number of nodules (<5, 6–10, or >10). The cerebrum, brain stem and cerebellum were analyzed to assess associated anomalies. Associations between PNH location and the presence of other anomalies were tested by using Fisher exact test and χ2 test. RESULTS: Posterior PNH were significantly associated with malformations of the cerebral cortex, diminished white matter volume, and mid-/hindbrain anomalies. Diffuse PNH were associated with diminished white matter volume, callosal “anomalies,” and the presence of megacisterna magna. Unilateral PNH were strongly associated with cortical malformations. CONCLUSIONS: Certain malformation complexes are associated with PNH in specific locations: posterior PNH with cerebral cortical and mid-/hindbrain malformations and diffuse PNH with callosal anomalies and megacisterna magna. Knowledge of these associations should allow more directed analyses of brain MR imaging in patients with PNH. In addition, knowledge of these associations may help to direct studies to elucidate the causes of these malformation complexes. aPNHanterior periventricular nodular heterotopiaCCcorpus callosumdPNHdiffuse periventricular nodular heterotopiaPNHperiventricular nodular heterotopiapPNHposterior periventricular nodular heterotopia